Molecular Analysis of Evolution and Origins of Cultivated Hawthorn (Crataegus spp.) and Related Species in China - Du, Xiao; Zhang, Xiao; Bu, Haidong; Zhang, Ticao; Lao, Yongchun; Dong, Wenxuan (Frontiers in Plant Science, 2019)
Abstract Hawthorn is of high economic value owing to its medicinal properties and health benefits. Crataegus is a member of the Rosaceae family; the genus has a complicated taxonomic history, and several theories on its origin have been proposed. In this study, 53 accessions from seven Crataegus taxa native to China and accessions of exotic Crataegus species (two from Europe and one from North America) were analyzed by specific locus amplified fragment sequencing (SLAF-seq). In total, 933,450 single-nucleotide polymorphisms were identified after filtering and used to investigate the species’ genomic evolution. Phylogenetic trees derived from nuclear simple sequence repeats and SLAF-seq data showed the same topology, in which C. maximowiczii and C. sanguineae formed a closely related cluster that was clearly separated from the cluster composed of C. hupehensis, C. pinnatifida, C. pinnatifida var. major, C. bretschneideri and C. scabrifolia. Phylogenetic and structure analysis indicated that the seven Chinese Crataegus taxa had two separate speciation events. Plants that evolved the southwestern route shared the genepool with the European species, whereas plants along the northeastern route shared the genepool with the North American species. TreeMix genetic analysis revealed that C. bretschneideri may have a hybrid origin. This study provides valuable information on the origins of Chinese Crataegus and suggests an evolutionary model for the main Crataegus species that native to China. Keywords: Hawthorn, Crataegus, SLAF-seq, nSSR marker, Molecular evolution